The Role Of Pancasila In View From The Sociology Of Religion In The Globalisation Era - Yusuf Yusuf (Journal of Business Social and Technology, 2023)
Globalization has positive and negative impacts on humans. The positive impact of course provides benefits for humans. However, the negative impact is incomparable and must be fortified especially for young Indonesians. Pancasila as the basis of the life of the Indonesian people plays an important role in fortifying the nation. This study aims to analyze the role of Pancasila in terms of the sociology of religion in the current era of globalization. The results show that Pancasila as the symbol of the state emphasizes the people to have a religion, belief in God Almighty and its rules and teachings. So that in this way, the practice of Pancasila values can protect humans from the various negative impacts of globalization. Humans will live by rules that are good and right according to the foundation of state life, namely Pancasila and the rules of God Almighty.